ANALISIS KINERJA LALU LINTAS PADA RUAS JALAN RAYA NEGARA SUMBAR - RIAU SEGMEN 2 KABUPATEN LIMA PULUH KOTA - Alfajri, Alfajri; Yermadona, Helga; Endri, Endri (Ensiklopedia Research and Community Service Review, 2024)
The Tanjung Pati area is crossed by the West Sumatra-Riau State Highway segment 2 with the function of an arterial road which is a busy access for vehicles to and from Riau Province. The research aims to analyze traffic volume, side obstacles, traffic performance, and proposed problem solving. Results of analysis of existing conditions Traffic Volume 1590.6 pcu/hour, Road Capacity 2017 pcu/hour, Degree of Saturation 0.79, Speed 30 km/hour, Service Level "D". To improve traffic performance, the first proposal was given, namely a parking ban with the installation of no parking signs, obtained a Road Capacity of 2318.4 pcu/hour, Degree of Saturation 0.69, Speed 37.73 km/hour, Service Level "C". Then the second proposal is to widen the road, so the Road Capacity is 2700.43 pcu/hour, Degree of Saturation 0.59, Speed 43.39 km/hour, Service Level "C". The results of the pedestrian analysis are the provision of sidewalk and pelican crossing facilities.Keywords: Volume; Capacity; Side Obstacles; Speed; Pedestrian.